Long-Term Outcomes of an International Cooperative Study of Intraoperative Radiotherapy Upfront Boost With Low Energy X-Rays in Breast Cancer - Sarria, Gustavo R.; Ramos, Maria L.; Palacios, Amalia; Del Castillo, Ruben; Castro, Felipe; Calvo, Angel; Cotrina, Jose M.; Heredia, Adela; Galarreta, Jose A.; Fuentes-Rivera, Paola; Avalos, Alicia; Martinez, David A.; et al. (Frontiers in Oncology, 2022)
Purpose To assess the effectivity of upfront kilovoltage intraoperative radiotherapy (IORT) as a boost in high-risk early-stage breast cancer patients from an international pooled cohort. Materials/Methods Patients from four centers in three different countries were retrospectively screened. Those with a minimum 1-year follow-up were included. Cumulative local- (LR), regional- (RR) and distant metastases rates (DM) were analyzed. Additionally, the estimated overall survival (OS) was assessed. The Cox regression analysis was performed to identify failure predicting factors. Results A total 653 patients from centers in Peru, Spain and Germany were included. The median follow-up was 55 (12-180) months and age was 58 (27-86) years. Clinical tumor (T) staging was T1 65.85%, T2 30.17% and T3 3.98%. Positive margins were found in 7.9% and in-situ component in 20.06%. The median IORT dose was 20 (6-20). Median time from IORT to EBRT was 74.5 (13-364) days. An overall 3.4% (n=22) of patients developed local recurrence at some point during follow-up. The 12-, 60- and 120-month cumulative LR were 0.3%, 2.3% and 7.9%, respectively. After multivariate analysis, only age < 50 remained to be a significant prognostic factor for local recurrence (HR 0.19, 95% CI 0.08-0.47; p<0.05) The 10-year estimated OS was 81.2%. Conclusion Upfront boost with IORT yields similar local control outcomes to those EBRT-based reports. Results from prospective trials, regarding toxicity, cosmesis and effectivity are awaited to confirm these findings.